Analisis Semiotika Gender dalam Film Perempuan Berkalung Sorban karya Abidah El Khalieqy - Asni, Asni; R. Kasau, M. Nurzin; Rasyid, Rustam Efendy (Nuances of Indonesian Language, 2024)
The background of the film raises the subject of gender discrimination in a conservative environment, highlighting the patriarchal culture that dominates and influences violence against women. Through a semiotic analysis of gender using Roland Barthes' theory, this research seeks to outline how the film portrays gender issues and the role of women in traditional society. It aims to examine the meaning of the movie using Roland Barthes' semiotic theory that explores the meaning of denotation, connotation, and myth. The method used in this research is qualitative method. The data collected are verbal and visual signs from the movie Perempuan Berkakung Sorban by Abidah El Kgalieqy. This study found 12 out of 309 scenes depicting gender issues and women's roles in traditional society using Roland Barthes' theory. The denotation of the scene displays gender injustice in everyday life. The connotations of the scenes reflect patriarchal views and gender discrimination through social and religious norms, reinforcing conservative domestic roles. The myth of women asserts that women should be subservient to men and that female leadership is against religious norms. The conclusion of this study highlights that patriarchal and conservative norms are used to maintain unequal power structures, limiting women's aspirations and freedoms in traditional societies.